Level of neighborhood environmental factors related to noncommunicable diseases in selected wards of urban Puducherry, South India - Gokul Sarveswaran; Yuvaraj Krishnamoorthy; Manikanda Nesan Sakthivel; Karthiga Vijayakumar; Yamini Marimuthu; Palanivel Chinnakali (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Noncommunicable diseases (NCDs) are the leading causes of mortality worldwide. Environmental factors play an important role in development of risk factors. Hence, the study was done to assess the neighborhood environmental factors related to NCDs in urban area. METHODOLOGY: This community-based cross-sectional study was carried out among three selected wards of urban Puducherry. All shops/establishments related to the risk of NCDs within the study area were study units. Information regarding tobacco, alcohol, diet, and physical activity-related establishments was assessed using pretested semi-structured pro forma. Shops/establishments were labeled either as "favorable" (prevents the risk of NCDs) or "unfavorable" (increases the risk of NCDs). RESULTS: Among 655 establishments, 372 (56.8%) belonged to favorable and 283 (43.2%) to unfavorable category, respectively. Tobacco-related establishments amount to 15.1% (95% confidence interval: 12.6-18.1) of the total establishments. Among these tobacco establishments, almost one-third were selling tobacco to minor and located within 100 m of school. Fruits and vegetable markets contributed to 21.8% of the total establishments. About 22% of the establishments were fast-food outlets. Public health sports facilities were only 6.8% of the total establishments. CONCLUSION: The current study reported almost equal distribution of favorable and unfavorable establishments. However, among unfavorable establishments, tobacco establishments raised concern as one-third of those were selling tobacco to minors. Healthy diet and physical activity related establishments were also found to be less. Hence, corrective measures are to be implemented which will reduce the burden of behavioral risk factors.